An investigation on use of paper mill sludge in brick manufacturing. (1st September 2017) - Goel, Gaurav; Kalamdhad, Ajay S.
Highlights: Fired bricks containing paper mill sludge (PMS) were produced. Mechanical and durability properties of bricks incorporating PMS was studied. Addition of PMS lead towards sustainable and economical construction. This study provided for the first time the behaviour of modulus of elasticity due to addition of organic waste content. Abstract: This paper reports the results of an exploratory experimental study to manufacture eco-friendly lightweight bricks through binary mix of paper mill sludge (PMS) and soil. The pre-manufacture activities include mineralogical, chemical, thermal and index properties characterisation of two kinds of soils (laterite and alluvial) and PMS. The mix ratio between PMS and soil was varied (0%, 5%, 10%, 15% and 20%) and two firing temperatures 850 °C and 900 °C were tested in order to emulate the typical conditions of a kiln. The performance of incorporating PMS into the mix was tested by evaluating properties such as linear shrinkage, compressive strength, water absorption, mass loss on ignition, and bulk density of bricks as recommended by the relevant Indian and ASTM standard codes. X ray diffraction results confirmed that the addition of PMS does not show any phase transformation and only enhances the porosity thereby leading to weight reduction. Based on the results, an optimum mix of 10% PMS with both soil types was found suitable for brick production at a firing temperature of 900 °C. Results obtained in this study will be helpful to brick industry for commercial production of PMS incorporated bricks leading to sustainable use of resources.